The proactive role played by sustainable wineries at times of economic crisis - Perez-Luno, Ana (My University, 2024)
Purpose – This paper analyses the behaviour of wineries after an economic crisis depending on their interest in the environment. Design/methodology/approach – A questionnaire was drawn up to collect quantitative data on Spanish wineries; a total of 230 firms participated in the study. Subsequently, a detailed statistical analysis was performed using the Mann–Whitney U test and rank sum. Findings – The results show that the wineries that were most interested in sustainability exhibited proactive behaviour during the post-crisis period, choosing to innovate in their different areas in order to deal with the situation. Practical implications – The paper develops a simple and effective method for wineries to gain confidence that their sustainable behaviour will be compatible with innovating and overcoming a crisis. Originality/value – This study contributes to the literature because, to the authors’ knowledge, no other study has investigated the concepts of sustainability, crisis and innovation simultaneously. The model is also applicable to international wineries as well as companies in other sectors and would help them to define their strategic and sustainability plans.
PUBLISHED
Keywords: Crisis, Sustainability, Innovation, Wineries, Spain; Smart & Sustainable Planet; Innovation; Sustainable Finance